Studi Awal Regenerasi Sowang (Xanthostemon novaguineense Valet.) - Sri Wilujeng; Verena Agustini (Jurnal Biologi Papua, 2017)
Sowang (Xanthostemon novaguineense Valet.) is an endemic plant of Cycloops and strictly distributed. Since years, the population of the plants is threatened by human activities through land conversion, forest burning and logging. There are only few seedling grow in Cycloops naturally. Sowang wood is known as a good quality, because of its inherent hardness and high density. Scienfific information about this species is remain unclear. Regarding the plant regeneration, it is also not enough information so far. The study was conducted at three places around Cycloops areas namely Waena, Doyo Baru (sowing habitat) dan Wambena (no sowang areas) of Jayapura Regency, Papua and also greenhouse of FMIPA Cenderawasih University. The experimental units were set up in a completely randomized design with 3 treatments. Each experiment was carried out in three replicated and each replicate includes 100 seeds. Data were analyzed by analysis of variance (ANOVA), followed by LSD α=0.05. The result showed that there is no relation between geographical distribution of Sowang at Cycloops and the phisical and chemical soil. All type of soil used in this study was good as media of the seed germination. Regarding the ratio of the sapling population, the germination is still low only 18%, the seedling only survive for 38 days after sowing. Key words: Cycloops, regeneration, Sowang, Papua.